Fatigue crack propagation analysis for multiple weld toe cracks in cut-out fatigue test specimens from a girth welded pipe. (January 2017) - Pang, John H.L.; Hoh, Hsin Jen; Tsang, Kin Shun; Low, Jason; Kong, Shawn Caleb; Yuan, Wen Guo
Highlights: Fatigue crack propagation analysis for multiple weld toe cracks was developed. Incorporates crack coalescence and crack closure for fatigue life prediction. Verified by four-point fatigue specimens cut-out from girth welded pipe. Crack shape development and coalescence of multiple cracks can be determined. Abstract: Multiple fatigue cracks are prevalent in welded structures. Current fatigue assessment code procedures employ various simplifications in the treatment of multiple cracks that result in over-conservative life predictions. In this work, crack coalescence and fatigue crack closure are incorporated into established models of crack propagation analysis. The model is verified by fatigue tests of cut-out welded steel pipes (butt weld) subject to four-point bending fatigue. A large number of starting weld toe cracks are determined from the experiments, with 12–22 cracks used in the fatigue life prediction of the fatigue tested pipes. The fatigue crack growth approach proposed is taken into account to predict remaining life more accurately compared to the threshold stress intensity factor approach used in the BS 7910 standard.